Avoiding 'de-plagiarism': Exploring the affordances of handwriting in the essay-writing process. (July 2019) - Wrigley, Stuart
This article discusses and challenges the increasing use of plagiarism detection services such as Turnitin and Grammarly by students, arguing that the increasingly online nature of composition is having a profound effect on student composition processes. This dependence on the Internet is leading to a strategy I term 'de-plagiarism', in which students copy/paste text into their essays and then 'cleanse' the text to avoid plagiarism detection. I then argue that this is being done in the context of an increasingly 'de-authored' writing environment, manifested by lack of formative writing development and anonymous marking, rendering the student invisible in the writing process. I then report on a phenomenon observed in class – namely that students who handwrote an exercise produced better, more original writing than those who typed, leading me to explore the affordances – via Bakhtinian notions of dialogicality and addressivity – of handwriting as a means of 're-authoring' the essay-writing process.